Fluoxetine counteracts the cognitive and cellular effects of 5-Fluorouracil in the rat hippocampus by a mechanism of prevention rather than recovery - Lyons, Laura; ELBeltagy, Maha; Bennett, Geoffrey; Wigmore, Peter (Public Library of Science, 2012)
5-Fluorouracil (5-FU) is a cytostatic drug associated with chemotherapy-induced cognitive impairments that many cancer patients experience after treatment. Previous work in rodents has shown that 5-FU reduces hippocampal cell proliferation, a possible mechanism for the observed cognitive impairment, and that both effects can be reversed by co-administration of the antidepressant, fluoxetine. In the present study we investigate the optimum time for administration of fluoxetine to reverse or prevent the cognitive and cellular effects of 5-FU. Male Lister-hooded rats received 5 injections of 5-FU (25 mg/ kg, i.p.) over 2 weeks. Some rats were co-administered with fluoxetine (10 mg/kg/day, in drinking water) for 3 weeks before and during (preventative) or after (recovery) 5-FU treatment or both time periods (throughout). Spatial memory was tested using the novel location recognition (NLR) test and proliferation and survival of hippocampal cells was quantified using immunohistochemistry. 5-FU-treated rats showed cognitive impairment in the NLR task and a reduction in cell proliferation and survival in the subgranular zone of the dentate gyrus, compared to saline treated controls. These impairments were still seen for rats administered fluoxetine after 5-FU treatment, but were not present when fluoxetine was administered both before and during 5-FU treatment. The results demonstrate that fluoxetine is able to prevent but not reverse the cognitive and cellular effects of 5-FU. This provides information on the mechanism by which fluoxetine acts to protect against 5-FU and indicates when it would be beneficial to administer the antidepressant to cancer patients.